(untitled) (Research, Society and Development, 2021)
POPBL is an active learning methodology centered on the student, in which, from a basic problem, the student research the contents related to the problem and proposes a project, which constitutes a final product of the learning process. This project is the result of the resolution of a problem situation created to put the student of Chemical Engineering, of the unit operations discipline, in contact with real problems of the chemical engineer profession, related to the process of separation of mixtures, using the techniques of transfer of mass as a promoter of this separation. In this work, students were encouraged to investigate their knowledge of chemical engineering to propose a sustainable, viable and low-cost project for the purification of water from the East River in Xintang, China. From experimental tests on the bed constructed and packed with biomass guava leaf, it was possible to calculate the time that the fixed bed can operate in cleaning the effluent, as well as the maximum adsorption capacity of this dye in the biomass, which was about 20 g of dye/kg of biomass, for beds operating in series. In terms of learning, the students reported that the project made it possible to develop other skills besides the technical knowledge of the discipline, such as group work, proactivity, sociability, empathy, communication skills and audio-visual expression. Thus, it is believed that the main objective of the project has been achieved.